Hypolipidemic Activity of Eryngium carlinae on Streptozotocin-Induced Diabetic Rats. (24th November 2011) - Noriega-Cisneros, Ruth; Ortiz-Ávila, Omar; Esquivel-Gutiérrez, Edgar; Clemente-Guerrero, Mónica; Manzo-Avalos, Salvador; Salgado-Garciglia, Rafael; Cortés-Rojo, Christian; Boldogh, Istvan; Saavedra-Molina, Alfredo
Abstract : Diabetes mellitus (DM) is a significant risk factor for the development of cardiovascular complications. This study was undertaken to investigate the effect of chronic administration of ethanolic extract of Eryngium carlinae on glucose, creatinine, uric acid, total cholesterol, and triglycerides levels in serum of streptozotocin- (STZ-) induced diabetic rats. Triglycerides, total cholesterol, and uric acid levels increased in serum from diabetic rats. The treatment with E. carlinae prevented these changes. The administration of E. carlinae extract reduced the levels of creatinine, uric acid, total cholesterol, and triglycerides. Thus administration of E. carlinae is able to reduce hyperlipidemia related to the cardiovascular risk in diabetes mellitus.